PENGARUH KUALITAS, LOKASI DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN RUMAH PADA PT. PUTERA KARYASINDO PRAKARSA - SARAH DESTARY SILABAN; HIKMAH . (JURNAL ILMIAH MAKSITEK, 2020)
In the world of marketing quality affects consumers in considering buying a product or service. Apart from quality, locationand service are also important. Strategic location and good service will make the demand for what is offered will increase butit is also inversely proportional if the location is not strategic and also the services provided are bad which will makeconsumers hinder their purchases. This study aims to determine the effect of quality, location and service on homepurchases at PT Putera Karyasindo Prakarsa. The data used in this study are primary data obtained through a questionnairewith a sample of 110 respondents from a population of 110 in 2019 that is distributed to consumers who make a homepurchase at PT Putera Karyasindo Prakarsa. The analytical method used is multiple linear regression analysis, using SPSSversion 22 which proves that quality, location and service have a positive effect on purchases with R Square value. Based onstatistical data, the indicators in this study are valid and the variables are reliable. The hypothesis of the t test shows thateach variable of quality, location and service significantly influences the purchase variable and has a t count greater than ttable. Then through the f test can be known that the quality, location and service variables simultaneously have an influenceon the purchase variable with the results of the calculated f value greater than f table.